Cyclo-pentyl-diphen-yl(4-thio-semi-carbazonopenta-noato-κO)tin(IV). - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2008)
The Sn atom in the title compound, [Sn(C(5)H(9))(C(6)H(5))(2)(C(6)H(10)N(3)O(2)S)], exists within a tetra-hedral geometry. The -NH(2) group forms a weak hydrogen bond across a center of inversion to the S atom of an adjacent mol-ecule, as well as another weaker hydrogen (across another center of inversion) to the Sn-bound O atom of another mol-ecule. The hydrogen-bonded layer structure is consolidated by a strong hydrogen bond between the -NH- group and the uncoordinated O atom of a third mol-ecule.